-2(x-4)(4-2)=0

Simple and best practice solution for -2(x-4)(4-2)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(x-4)(4-2)=0 equation:



-2(x-4)(4-2)=0
We add all the numbers together, and all the variables
-2(x-4)2=0
We multiply parentheses
-4x+16=0
We move all terms containing x to the left, all other terms to the right
-4x=-16
x=-16/-4
x=+4

See similar equations:

| 3(a-2)²=3(a²-4a+4) | | (D^3+D^2+D)y=0 | | X-(17-4x)=(3x+14)-(11-3x) | | -1.6x+5.6=-4.8 | | 2w+4=3w+16 | | 3x-6=117 | | 15k-10k^2=0 | | -7x+4=30 | | -6x+14=-28 | | 4x+8=-41-3 | | 3x+x+52=221 | | 100=x-(x*0.04) | | F(x)=x+1/× | | 5s-8=7+2s | | 3x+15-57+x=11 | | 6x+28=14x+68 | | 5x+7=2x+13.X= | | 2x+5=9x+13 | | 5(4w+8)/2=-5 | | -8-3x=-16+13x | | 2x–3=x–(3x–5) | | 5x+7=2x+13X= | | 5+2k/7=-1 | | X+1/2+2x+3/3=5 | | 10(x-5)=-5(x+4)+30 | | -8(s+5)=-100 | | 5(2x+3)-6(x-3)=47 | | 8(x-4)=4(x-9)+16 | | 7y+1+4y+14=180 | | 2(4×+3)=6x+14 | | 7y+1=4y+14 | | 7=m+1m= |

Equations solver categories